Fundamentals of Magneto-Optical Spectroscopy - Sato, Katsuaki; Ishibashi, Takayuki (Frontiers in Physics, 2022)
This paper provides comprehensive review on magneto-optical (MO) spectroscopy. In the first place, different methods of MO measurements such as Faraday effect, MO Kerr effect, Cotton-Mouton effect are briefly introduced. Next, macroscopic and microscopic origin in magnetic materials is summarized. In the third place, measuring techniques for MO spectroscopies are reviewed, with a particular reference to the polarization modulation technique, and examples of MO spectra in various materials with interpretation in terms of electronic structures of materials are introduced. Finally, recent MO phenomena in topological materials are introduced.